Nilai Sosial dan Identitas Budaya dalam Tradisi Gendang Belek Masyarakat Desa Suradadi - Candra Ulfiana; Dedi Kiar (Lembaga Publikasi Ilmiah Nusantara, 2026)
The Gendang Belek tradition is one of the cultural heritages of the Sasak community that carries strong social values and cultural identity in rural life. This community service activity aims to identify, document, and strengthen public understanding of the social values and cultural identity embedded in the Gendang Belek tradition in Suradadi Village.The methods used in this activity include a participatory approach through field observations, interviews with traditional leaders, local artists, and community members, as well as conducting focus group discussions and cultural outreach programs for the younger generation.The results of the activity show that the Gendang Belek tradition functions not only as a medium of entertainment and artistic performance but also as a means of strengthening social solidarity, fostering a sense of togetherness, and reinforcing the cultural identity of the Sasak community. In addition, this tradition plays an important role in the transmission of cultural values to the younger generation through active participation in training and performances.However, modernization and the influence of popular culture present challenges to the preservation of this tradition. Therefore, this community service initiative encourages collaborative efforts among the community, village government, and educational institutions to ensure the sustainability of the Gendang Belek tradition through training programs, cultural documentation, and the integration of local cultural values into educational and social activities.Thus, the Gendang Belek tradition is expected to remain preserved as part of the cultural identity of the people of Suradadi Village.